Case Report: Aspergillus fumigatus-associated plastic bronchitis in a pediatric patient with cystic fibrosis complicated by allergic bronchopulmonary aspergillosis - Liu, Fen; Zhao, Linlin; Gao, Yanpeng; Wang, Xiaoyan; Zhang, Han (Frontiers in Pediatrics, 2025)
While plastic bronchitis (PB) is most commonly associated with viral pathogens and Mycoplasma pneumoniae (MP) infections, fungal etiologies are exceptionally uncommon in children. We described a case of a 10-year-old girl with Aspergillus fumigatus-induced PB. She had a 10-month history of intermittent coughing as the predominant symptom, without acute progressive dyspnea. Her medical history included cystic fibrosis (CF) complicated by allergic bronchopulmonary aspergillosis (ABPA). The bronchoscopy revealed a large amount of thick, gelatinous mucus plugs in the right lower lobe bronchus. After two fiberoptic bronchoscopy procedures, the plugs were removed and turned out to be large gelatinous bronchial casts. Fungal culture of the bronchoalveolar lavage fluid (BALF) was positive for Aspergillus fumigatus, and pathological examination of the bronchial casts revealed Aspergillus hyphae. This case demonstrates a chronic onset process, with significantly delayed cast formation compared to PB cases caused by other pathogens. Notably, Aspergillus fumigatus-associated casts exhibited marked differences in CT imaging characteristics, gross morphological features and histopathological profiles when compared to MP-associated casts. The current case suggests that Aspergillus fumigatus may be an additional cause of PB. Clinicians should include this pathogen in the differential diagnosis of patients presenting with prolonged symptom duration, CT evidence of high-attenuation mucus plugs and casts exhibiting gelatinous texture.